2020
DOI: 10.3386/w27592
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in COVID-19: Evidence from Six Large Cities

Abstract: Yelowitz acknowledges support from University of Kentucky's Institute for the Study of Free Enterprise. We thank Chris Bollinger, Bill Hoyt, and James Ziliak for helpful comments. We thank SafeGraph for providing access to the data. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
(15 reference statements)
0
5
1
Order By: Relevance
“…Given the crucial role of private beliefs in shaping behavior, an important question is how individual beliefs are formed and whether they reflect reality. Unlike prior work in the context of COVID-19 (Bordalo et al 2020), we find that differences in the perception of risks across demographic subgroups and different geographies generally correlate with known realities of the risk of contracting the disease (Benitez et al 2020; Ford et al 2020; Richardson et al 2020; Polyakova et al 2020; Polyakova et al 2021). This finding of a positive relationship between risk perceptions and protective behaviors in the context of the COVID-19 pandemic is consistent with other contemporaneous studies (Dryhurst et al 2020; Heffetz and Ishai 2021).…”
Section: Discussioncontrasting
confidence: 97%
“…Given the crucial role of private beliefs in shaping behavior, an important question is how individual beliefs are formed and whether they reflect reality. Unlike prior work in the context of COVID-19 (Bordalo et al 2020), we find that differences in the perception of risks across demographic subgroups and different geographies generally correlate with known realities of the risk of contracting the disease (Benitez et al 2020; Ford et al 2020; Richardson et al 2020; Polyakova et al 2020; Polyakova et al 2021). This finding of a positive relationship between risk perceptions and protective behaviors in the context of the COVID-19 pandemic is consistent with other contemporaneous studies (Dryhurst et al 2020; Heffetz and Ishai 2021).…”
Section: Discussioncontrasting
confidence: 97%
“…Moving beyond the baseline specification, I introduce a set of additional variables that have been highlighted in the literature as potential drivers of the local COVID-19 toll (Panel B, Table 1). US-based research has found a connection between worse local COVID-19 outcomes and lower schooling levels, or the presence of racial minorities Benitez et al, 2020;Wiemers et al, 2020). These factors could play an even more important role in Brazil, given the country's long history of racial disparities and inequalities in access to higher education.…”
Section: Results At the End Of The First Year Of The Pandemicmentioning
confidence: 99%
“…It also limits our statistical power to detect potentially important differences across subgroups. Future research, with larger sample sizes, could beneficially compare differences in program participation based on residence in areas experiencing higher COVID-19 case rates [28]. Third, as with all surveys on public program participation, there is likely to be some under-identification of program participation [29].…”
Section: Discussionmentioning
confidence: 99%